IMPROVING STUDENTS' CONCEPTUAL UNDERSTANDING AND CRITICAL THINKING SKILLS THROUGH WORDWALL EDUCATIONAL GAMES IN ELEMENTARY SCHOOL - Vera Idayani; Syifa Saputra; Afkar Afkar (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2026)
The swift evolution of digital technology in the domain of primary education has reshaped instructional methods of innovative, interactive, and effective learning media. In this regard, Wordwall-based educational games are viewed as a promising tool to significantly improve students’ conceptual understanding as well as their critical thinking skills. This research was conducted to investigate the effectiveness of Wordwall educational games in enhancing elementary school students’ comprehension of concepts and their critical thinking abilities. The study employed a quantitative approach with a quasi-experimental method, specifically utilizing a non-equivalent control group design. The participants consisted of elementary school students who were divided into two groups: an experimental group and a control group. The experimental group was taught using Wordwall-based educational games, while the control group received instruction through traditional teaching methods. Data were collected using test instruments in the form of pre-tests and post-tests, which were designed to measure students’ conceptual understanding and critical thinking skills. The instruments were developed based on predetermined learning indicators and were validated by experts before being administered. Following rigorous statistical screening via normality and homogeneity tests, an independent samples t-test confirmed that the experimental group attained markedly superior post-test results in critical thinking and conceptual understanding compared to the control group. These findings demonstrate that the implementation of Wordwall educational games has a positive and by demonstrating a statistically significant influence on students' cognitive growth, Wordwall proves to be a robust digital medium that effectively facilitates higher-order thinking within primary school settings.